Redox activation of ATM enhances GSNOR translation to sustain mitophagy and tolerance to oxidative stress. (27th November 2020) - Cirotti, Claudia; Rizza, Salvatore; Giglio, Paola; Poerio, Noemi; Allega, Maria Francesca; Claps, Giuseppina; Pecorari, Chiara; Lee, Ji‐Hoon; Benassi, Barbara; Barilà, Daniela; Robert, Caroline; Stamler, Jonathan S; et al.
Abstract: The denitrosylase S ‐nitrosoglutathione reductase (GSNOR) has been suggested to sustain mitochondrial removal by autophagy (mitophagy), functionally linking S ‐nitrosylation to cell senescence and aging. In this study, we provide evidence that GSNOR is induced at the translational level in response to hydrogen peroxide and mitochondrial ROS. The use of selective pharmacological inhibitors and siRNA demonstrates that GSNOR induction is an event downstream of the redox‐mediated activation of ATM, which in turn phosphorylates and activates CHK2 and p53 as intermediate players of this signaling cascade. The modulation of ATM/GSNOR axis, or the expression of a redox‐insensitive ATM mutant influences cell sensitivity to nitrosative and oxidative stress, impairs mitophagy and affects cell survival. Remarkably, this interplay modulates T‐cell activation, supporting the conclusion that GSNOR is a key molecular effector of the antioxidant function of ATM and providing new clues to comprehend the pleiotropic effects of ATM in the context of immune function. Synopsis: Hydrogen peroxide and pro‐oxidant conditions activate ATM via oxidation of Cys2991. The resulting phospho‐signal activates CHK2 and p53 and culminates in enhanced translation of the denitrosylase GSNOR to sustain mitophagy and protect the cells against oxidative stress. GSNOR expression is induced by H2 O2 at the translational level via the redox activation of an ATM/CHK2/p53 signaling axis. GSNOR is exclusively required to sustain mitophagy induced by pro‐oxidant conditions, such as H2 O2 or CCCP. ATM/GSNOR‐sustained mitophagy is essential to maintain viability in cells subjected to severe oxidative stress, or to a double oxidative hit, such as the coupling of an H2 O2 burst to concomitant NO fluxes observed during lymphocyte activation. ATM and GSNOR inhibition results in increased cell death and reduced T cell‐to‐blast activation upon stimulation, providing a rationale to explain why A‐T patients, as well as Atm −/− and Gsnor‐null mice show the same immune phenotype, i.e., a reduced number of CD4 + cells. Abstract : Hydrogen peroxide and pro‐oxidant conditions activate ATM via oxidation of Cys2991. The resulting phospho‐signal activates CHK2 and p53 and culminates in enhanced translation of the denitrosylase GSNOR to sustain mitophagy and protect the cells against oxidative stress.